La interculturalidad y las percepciones actitudinales - Acosta Cárdenas, Sofia del Carmen (2025)
The objective of this research is to determine the importance of interculturality and the attitudinal perceptions of fifth-grade students at the Fe y Alegría elementary school, the methodology employed was qualitative research, utilizing an observation checklist with eight indicators addressing key aspects of interculturality and an interview guide for the teacher regarding attitudinal perceptions. The study population consisted of 34 students. belonging to the fifth year of basic education, the design was non experimental, since the variables were not manipulated, making this research exploratory and descriptive. The results obtained were analyzed using tables where the responses for each question are represented. This allowed for the identification of a positive and majority perspective regarding interculturality, its respect, and support. This study revealed the importance of interculturality and also highlighted the challenges and needs for cultural interaction, thus identifying the most relevant aspects that are currently being sough. Promoting the correct application of attitudinal perceptions so that they can be included in lesson planning. In conclusion, the interculturality of attitudinal perceptions in the group studied is of great importance, as it allows for the integration of new methodologies and pedagogical approaches that are innovative and relevant for cultural interaction in the classroom and fosters respect and empathy correctly with innovative methods that benefit all students.